Bio-inspired iron-catalyzed oxidation of alkylarenes enables late-stage oxidation of complex methylarenes to arylaldehydes - Penghui Hu (Nature Portfolio, 2019)
Oxidation of toluenes to benzaldehydes is usually accompanied by overoxidation products. Here, the authors report an iron-catalysed aerobic oxidation of methylarenes to benzaldehydes with high yields and selectivities, even in presence of boronic acid groups and in complex natural products and drugs.